An Efficient VBA Spreadsheet Algorithm and Model for the System Optimum Traffic Assignment - Jeong, Ki-Young; Hong, Jae-Dong; Xie, Yuanchang (International journal of applied industrial engineering, 2012)
The traffic assignment involves assigning traffic to a transportation network consisting of highways, arterials, or transit routes. To obtain an optimal traffic assignment scheme, a mathematical program (MP) should be formulated and solved. The process of formulating an MP requires identifying all possible paths connecting each origin-to-destination pair through the network, since the number of those paths turns out to be the number of the decision variables. Consequently, formulating and solving such an MP is difficult due to the large number of the decision variables and constraints. For that reason, practitioners prefer heuristics for a large-scale transportation network. In this paper, the authors suggest a new and efficient way of formulating an MP and develop a Microsoft Excel model with Visual Basic for Applications (VBA) to find the optimal assignment scheme for the traffic assignment problem. The developed Excel model with VBA can be easily expanded to a large-scale transportation network.